Investigating conference feedback in Cambodian EFL class: students’ writing accuracy improvement and their views of the feedback - Chan Hum (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2021)
Research of conference feedback on EFL students' writing accuracy is a vital issue; however, it has never been conducted in Cambodia. This study was carried out to fill this void by investigating conference feedback to improve students' writing accuracy in four categories: semantic, grammatical, mechanic, and lexical features. It also explored the students' perceptions of the feedback in the context of EFL writing class. One class, with twelve students, from 18 to 25 years of age, with a ratio of 8:4 women: men, was purposively chosen for the study which was designed in two cycles, each with eight steps. Data were collected from the writing tests, writing assignments, students' self-evaluation survey, and focus-group discussions. Findings revealed that conference feedback had improved students' writing skills by allowing them to use correct grammar and expressions. The feedback has also developed students' engagement in the writing process. It also proposed a pedagogical implication that effective feedback through a conference approach depends to a great extent on the knowledge and experience of the teacher, classroom resources, and interactions between the teacher and the student.